Comparison of the Efficacy of Entecavir and Tenofovir in Reducing Hepatocellular Carcinoma Risk in Chronic Hepatitis B Patients: A Real-Life Study in Turkey - Fatih Güzelbulut; Pınar Gökçen; Güray Can; Gupse Adalı; Ayça Gökçen Değirmenci Saltürk; Ekrem Aslan; Kamil Özdil; Hamdi Levent Doğanay (Turkish Journal of Gastroenterology, 2021)
Background: It is controversial whether entecavir or tenofovir differs in reducing hepatocellular carcinoma (HCC) risk. We aimed to compare the efficacy of entecavir and tenofovir in reducing HCC risk in chronic hepatitis B (CHB) patients. Methods: This retrospective study included 607 nucleos(t)ide naive CHB patients who had received entecavir or tenofovir. Patients who developed HCC during the first 12 months of therapy were excluded. Cumulative HCC incidences at years 2, 3, 4, 5 and 10 were compared between entecavir and tenofovir groups. Factors associated with HCC were determined by univariate and multivariate analyses. Results: Nineteen (3.1%) patients developed HCC, 12 (4.8%) in entecavir group and 7 (1.9%) in tenofovir group (P = .045). In the entire cohort, cumulative HCC incidences at years 2, 3, 4, 5 and 10 were 1.8%, 2.9%, 4.4%, 5.2% and 9.9% in entecavir group, and 0.6%, 2.4%, 2.4%, 2.4% and 3.7% in tenofovir group, respectively (log-rank P = .130). In multivariate analysis, age ≥50 years, cirrhosis, decompensated cirrhosis, high GGT and low platelet levels were associated with HCC in the entire cohort. In advanced fibrosis/cirrhosis cohort, cumulative HCC incidences at years 2, 3, 4, 5 and 10 were 4.6%, 7.1%, 8.6%, 12.1% and 15.5% in entecavir group, and 1.8%, 5.6%, 5.6%, 5.6% and 8.5% in tenofovir group, respectively (log-rank P = .267). In multivariate analysis, age ≥50 years, decompensated cirrhosis, high GGT and low platelet levels were associated with HCC in the advanced fibrosis/cirrhosis cohort. Conclusion: Entecavir and tenofovir are similarly effective in reducing HCC risk in CHB patients. Cite this article as: Güzelbulut F, Gökçen P, Can G, et al. Comparison of the efficacy of entecavir and tenofovir in reducing hepatocellular carcinoma risk in chronic hepatitis B patients: A real-life study in turkey. Turk J Gastroenterol. 2021; 32(4): 412-421.